Fusopoltide A and fusosterede A, A polyketide with a pentaleno[1, 2-c]pyran ring system and A degraded steride, from the fungus Fusarium solani. Issue 27 (4th July 2018) - Chen, Keliang; Sun, Weiguang; Bie, Qiong; Liu, Xiulan; Chen, Chunmei; Liu, Junjun; Xue, Yongbo; Wang, Jianping; Luo, Zengwei; Zhu, Hucheng; Zhang, Yonghui
Graphical abstract: Highlights: A novel polyketide and a new steride degraded were isolated from the Fungus Fusarium solani . The absolute configurations were elucidated by X-ray crystallographic analysis and ECD method. Biosynthesis of the novel polyketide, fusopoltide A (1 ), was proposed. Target prediction and molecular docking revealed strong interaction between fusopoltide A (1 ) and COX-2. COX-2 inhibitory activities of fusopoltide A (1 ) and fusosteride A (2 ) were evaluated in vitro. Abstract: Fusopoltide A (1 ), a novel polyketide featured a pentaleno[1, 2- c ]pyran ring, and fusosteride A (2 ), a new steride with A/B-ring degraded, together with a known ergosterol peroxide (3 ), were isolated from a solid culture extract of Fusarium solani . The structures of1 and2 were elucidated by detailed interpretation of their HRESIMS and NMR spectroscopic data and their absolute configurations were determined by X-ray crystallographic analysis and the electronic circular dichroic (ECD) method, respectively. The postulated biogenetic pathways of1 and2 were also discussed. Compound1 exhibits inhibitory activity against cyclooxygenase-2 (COX-2) with an IC50 value of 3.45 μM.